2017
DOI: 10.1021/acsbiomaterials.7b00854
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Evaluation of Multiphase Ultrahigh Ductility Mg–Li–Zn Alloys for Cardiovascular Stent Application

Abstract: Magnesium alloys have been extensively studied as a novel biodegradable metallic material for cardiovascular stent application. However, the ductility limitation of magnesium alloy has been a key issue for biodegradable stents applications. In this study, two different multiphase ultrahigh ductility Mg–Li–Zn alloys, LZ61 and LZ91, are fabricated in the form of extruded rods and evaluated both in vitro and in vivo. The microstructure, mechanical properties and in vitro degradation are evaluated as well as in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 62 publications
2
33
2
Order By: Relevance
“…Therefore, LZ61-KBMS were better protected under the flow environment, displaying a much slower corrosion rate. Figure 7 summarizes the corrosion rates of LZ61-KBMS alloy and AZ31 alloy under different tests based on the current study and our previous publications 31 . Since AZ31 stents were not implanted in vivo herein, no results of AZ31 in vivo stent degradation rates are plotted in Fig.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Therefore, LZ61-KBMS were better protected under the flow environment, displaying a much slower corrosion rate. Figure 7 summarizes the corrosion rates of LZ61-KBMS alloy and AZ31 alloy under different tests based on the current study and our previous publications 31 . Since AZ31 stents were not implanted in vivo herein, no results of AZ31 in vivo stent degradation rates are plotted in Fig.…”
Section: Discussionmentioning
confidence: 77%
“…In vitro degradation of LZ61 stent in a bioreactor. We earlier published the degradation of our novel LZ61 alloy matching AZ31 under static environments 31 . However, in vivo, tracheal stents are exposed to a dynamic fluid environment with moving mucus consistently cleaning the airway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The in vitro result reported by Cheng et al indicated that Mg does not present any cytotoxic effects on L929 and ECV304 cells [4]. The in vivo study also showed that Mg/Mg alloys are biocompatible [5]. (2) Good mechanical properties: Mg alloys have similar strength and elastic modulus with natural bones, and have the potential to minimize stress shielding [6,7].…”
Section: Introductionmentioning
confidence: 97%